Opinions and preferences of British Columbia pharmacists and physicians on medication management services. (January 2017) - Tsao, Nicole W.; Khakban, Amir; Gastonguay, Louise; Zafari, Zafar; Lynd, Larry D.; Marra, Carlo A.
Background: Medication management (MM) services are being provided by pharmacists across Canada in various forms, but pharmacist-physician collaboration is still not a routine practice in most jurisdictions. This survey aimed to gather pharmacists' and physicians' opinions and preferences for MM provision. Methods: Two parallel, cross-sectional online surveys, including best-worst scaling tasks, were designed for pharmacists and physicians in British Columbia to capture and compare their preferences for a number of attributes of MM. Results: Surveys were completed by 119 pharmacists and 146 physicians. Results indicate that pharmacists and physicians had similar opinions on many aspects of MM. Ninety-five percent of pharmacists and 69% of physicians believed that additional health services are needed to help patients optimize the use of their medications. However, the majority of each group felt that they were the most important health care professional in providing this service. Most pharmacists (79%) and some physicians (25%) thought that optimizing use of medications would result in both decreased costs and utilization to the health care system. Both pharmacists and physicians felt that the best attribute of an MM service would be if the services resulted in improved health and medication use for patients. Both groups were motivated by increased remuneration for MM; however, the relative strength of preference for this was higher among physicians. Interestingly, physicians valued improved medication adherence as a result of MM more highly than pharmacists did. Discussion and Conclusion: Most pharmacists and physicians agreed that improving patients' health and medication use would be the best attribute of MM and that there is a need for such services. However, physicians also had strong preferences for being remunerated for participating in MM provision.